Penerapan Metode Prototype Pada Perancangan Sistem Informasi Penjualan Aksesoris Kamera Berbasis Web - Puspita, Ari; Yuningsih, Yuyun; Mazia, Lia; Pujiastuti, Endang (Fakultas Teknik Universitas Hamzanwadi, 2024)
The sale of camera accessories is one of the important components in business. However, currently the company faces several obstacles in the sales process. In addition, there is no system that suits the needs of customers in gaining access to camera accessories sold. To overcome this problem, this study aims to design and develop a prototype interface mockup design system for selling camera accessories. This research uses a prototype system development method by identifying user needs, analyzing existing sales processes, and designing appropriate solutions. Through needs analysis, it is known that customers need convenience in searching for products, seeing product details, making purchases. Meanwhile, admins need to have access to manage inventory, process orders, and view sales reports. The purpose of this study is to design a system based on customer needs so that it is expected to increase satisfaction in using the system. In addition, it is expected that this system can be the basis for further development towards integration with wider ecommerce platforms. The results of this system design can be used as reference material to develop a sales system